Mouse lung‐adapted mutation of E190G in hemagglutinin from H5N1 influenza virus contributes to attenuation in mice. Issue 11 (30th July 2015) - Han, Pengfei; Hu, Yi; Sun, Wei; Zhang, Sen; Li, Yuchang; Wu, Xiaoyan; Yang, Yinhui; Zhu, Qingyu; jiang, Tao; Li, Jing; Qin, Chengfeng
<x xml:space="preserve">Abstract</x> The highly pathogenic H5N1 avian influenza virus is one of the greatest influenza pandemic threats since 2003. The association of the receptor binding domain (RBD) with the virulence of influenza virus is rarely addressed, particularly of H5N1 influenza viruses. In this study, BALB/c mice were intranasally infected with A/Vietnam/1194/2004 (VN1194, H5N1). The mouse lung‐adapted variants were isolated and the mutation of E190G (H3 numbering) in the RBD was recognized. The recombinant virus, rVN‐E190G carrying E190G in hemagglutinin (HA) was designed and rescued using reverse genetics techniques. The receptor binding activity, growth curve and pathogenicity in mice of the rVN‐E190G were investigated. Results demonstrated that rVN‐E190G virus increased the binding avidity to α2, 6 SA (sialic acid) and reduced the affinity to α2, 3 SA, meanwhile weakened the viral replication in vitro. Moreover, the virulence assessment demonstrated that rVN‐E190G was attenuated in mice. These results indicated that the mutation E190G in HA decreases H5N1 viral replication in vitro and significantly attenuates virulence in vivo. These findings identify one of the determinants in RBD which can be associated with H5N1 virulence in mice. J. Med. Virol. 87:1816–1822, 2015. © 2015 Wiley Periodicals, Inc.